Three New Species of Velvety Shore Bugs (Hemiptera: Heteroptera: Ochteroidea) From Mid-Cretaceous Kachin Amber Shed Light on the Evolution of Rostrum Length in Ochteroidea - Zhang, Mao; Zhao, Zhipeng; Ren, Dong; Yao, Yunzhi (Frontiers in Ecology and Evolution, 2022)
Two new genera of velvety shore bugs, Arcochterus Zhang, Ren & Yao gen. nov., Parvochterus Zhang, Ren & Yao gen. nov. with three new species, Arcochterus fuscus Zhang, Ren & Yao sp. nov., Parvochterus reticulatus Ren & Yao sp. nov. and P. lanceolarus Zhang, Ren & Yao sp. nov. are described. Based on the combination of fossil and extant taxa, a cladistic analysis is conducted to confirm the phylogenetic position of these species and allows reconstruction of the inter-genus relationships within the superfamily Ochteroidea. Major conclusions of the phylogenetic analysis: (1) these new species and Grimaldinia pronotalis Popov & Heiss, 2014 belongs to Ochteridae; (2) Ochteroidea is a monophyletic group, Ochteridae and Gelastocoridae are sister groups and monophyletic, respectively. (3) The ancestral character state reconstruction (ACSR) shows that the length of rostrum has occurred at least thrice independent transitions during the evolution of the superfamily Ochteroidea.